IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH INSECURITY PADA SISWA SMAN 01 PALANGKA RAYA - Surawan Surawan; Salsabila Asyifana DLT (Kuttab : Jurnal Ilmu Pendidikan Islam, 2022)
This article aims to look at implementing Islamic Religious Education learning at the high school level, especially in the faith in qada and qadar chapter, to prevent insecurity in students. This article is motivated by the phenomenon of students of SMAN 1 Palangka Raya in the form of feelings of insecurity and inferiority towards others. The results of this study found that applying Islamic Religious Education lessons on the theme of believing in qada and qadar can be an alternative in preventing the emergence of a sense of insecurity in adolescents, especially students. Insecurity arises because of a lack of understanding of Allah's decree. So, in its application, students can appreciate and practice learning materials in everyday life.